Recruiter’s Strategy for Identifying Hybrid Skills in Job Applicants - Richa Afriana Munthe; Sopiah Sopiah (Indonesian Journal of Multidisciplinary Science, 2021)
In this digital era, hybrid skills are needed to enable people to add value beyond the application of technology (Technical skills). However, organizations will always be run by humans, not robots. They work in an organization requires communication skills, collaboration, empathy, and so on. It is important for a recruiter to get talents with hybrid skills combined with qualified technical and non-technical skills. The research design used is the literature review method. Therefore, the nature of this research is descriptive analysis, by revealing, describing, and explaining related to the research topic, namely the analysis of how recruiters identify the capacity of hybrid skills in candidates through regular analysis of the literature that has been obtained. Hybrid skill is considered more capable of describing the workforce in completing tasks with maximum performance. In the labor recruitment process, companies have problems in the labor market that do not meet the qualifications of the soft skills and hard skills of each applicant are not balanced. In order for companies to improve the skills of workers efficiently and utilize their talents more effectively, they must be able to identify both the skills workers already have and those they will need.